2022
DOI: 10.1097/bor.0000000000000919
|View full text |Cite
|
Sign up to set email alerts
|

The impact of omics research on our understanding of osteoarthritis and future treatments

Abstract: Purpose of reviewTo review recent studies using Omics approaches (genomics, proteomics, metabolomics, single cell analyses) in patient populations and animal models of osteoarthritis (OA), with the goal of identifying disease-modifying mechanisms that could serve as therapeutic and diagnostic targets. Recent findingsThe number of genes, pathways and molecules with potential roles in OA pathogenesis has grown substantially over the last 18 months. Studies have expanded from their traditional focus on cartilage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…While an abundance of genetic variants associated with OA have been detected, research is limited by the fact that the majority of these variants are found within non-coding regions of the genome and have a small effect size [ 4 , 12 ]. This has led to the prevailing theory that the accumulation of multiple risk alleles contributes to the predisposition of OA later in life and that a threshold must exist that tips an individual into OA.…”
Section: Discussionmentioning
confidence: 99%
“…While an abundance of genetic variants associated with OA have been detected, research is limited by the fact that the majority of these variants are found within non-coding regions of the genome and have a small effect size [ 4 , 12 ]. This has led to the prevailing theory that the accumulation of multiple risk alleles contributes to the predisposition of OA later in life and that a threshold must exist that tips an individual into OA.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of circulating miR biomarkers [ 203 ] using unbiased sequencing and other omics-based approaches (genome-wide association studies [ 204 ], proteomics [ 205 ], metabolomics [ 206 ]) may provide deeper insights into patient endotype. The use of AI algorithms and bioinformatics to cohesively knit large omics datasets [ 207 ] to systematically classify patient endotypes can further advance the field. Organ-on-chip technology, which can incorporate patient-specific blood, synovial fluid, urine and/or tissue biopsy samples, offers the dual potential of providing patient baseline disease endotype information and surrogate in vitro readouts of the efficacy of various drugs or test therapeutics [ 208 ].…”
Section: Roadmap For Successful Msc Oa Trialsmentioning
confidence: 99%
“…Recent advances in understanding complex disease have been greatly enhanced by the application of multi-omic approaches to disease relevant tissues [11, 18] . The strengths of these approaches are the focus on human disease cohorts at scale (hundreds to tens of thousands of participating individuals), the unbiased and systematic nature of molecular identification, the ability to map molecules to a shared pathway, and the ability to replicate results across independent cohorts.…”
Section: Introductionmentioning
confidence: 99%